Assessing Solid Catalysts with Ionic Liquid Layers (SCILL) from Molecular Dynamics Simulations: On the Role of Local Charge Polarization - Trzeciak, Simon; Zahn, Dirk (Chemistry - A European Journal, 2024)
Recent developments in molecular mechanics modelling of metal catalyst surfaces with interfaces to complex ad-layers or bulk liquids enable the study of 10 nm scale systems by molecular dynamics simulations of up to microseconds. Therein, electronic polarization as otherwise benchmarked by quantum calculations is mimicked via atom-centered partial charges that are adjusted dynamically to account for changes in local environment. Apart from thermal fluctuations, this encompasses molecule association and dissociation processes as well as externally applied voltage. Here, we elaborate the concept of employing the charge equilibration method to the molecular dynamics simulation of solid catalysts, namely metal surfaces and substrate-supported metal nanoparticles. This showcases the association of reactants and their interplay with local charge polarization upon co-adsorption of ionic liquids or application of external voltage – thus paving the way to understanding complex interfaces in (electro−)catalysis from molecular dynamics simulation.
CRIS-Team Scopus Importer:2024-10-18
Keywords: Heterogeneous catalysis; Ionic liquids; Molecular simulation